Remarks by World Bank Group President David Malpass at the 2022 Ibrahim Governance Forum - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass at the 2022 Ibrahim Governance Forum on May 25, 2022. He spoke about the world is facing a dangerous period of overlapping crises of the COVID-19 pandemic, inflation, debt, and Russia’s invasion of Ukraine. He explanied that Africa is particularly vulnerable to the impacts of the overlapping crises. He spoke about climate interventions and projects offer large global public good benefits, but many require substantial external funding as well as a comprehensive policy framework. He emphasized the importance of strong governance and sound institutions to confronting climate challenges in Africa, the area which is at the core of the Mo Ibrahim Foundation’s work. He highlighted that the Ibrahim Index of African governance is vital in understanding the overall trajectory of governance in Africa and informing decision-making processes, including in response to climate change. He said that building a more climate-resilient Africa does not mean slowing down development or the progress toward achieving SDG7. He concluded by saying that various steps will be essential in Africa’s transition from subsistence farming to productive economic activity in agriculture, services, industry, and public sectors.